Religious Moral Beliefs Inversely Related to Trauma Experiences Severity and Presented Posttraumatic Stress Disorder Among Bosnia and Herzegovina War Veterans - Hasanovic, Mevludin (Journal of religion and health, 2015)
The aim of this study was to determine the correlation of the level of religious moral beliefs (RMB) with trauma experiences and posttraumatic stress disorder (PTSD) severity in war veterans of Bosnia and Herzegovina. The sample consists of 120 Bosnian war veterans divided into two equal groupsone with and one without PTSD. We used the Harvard Trauma Questionnaire and the RMB belief scale. We then correlated the severity of trauma experiences and PTSD symptoms with veterans scores on the RMB scale. The score on the RMB scale was negatively correlated to severity of trauma experiences and PTSD symptoms (Pearsons r = -0.509, P = 0.004; Pearsons r = -0.325, P < 0.001, respectively). The RMB may have protective role in the mental health stability of severely traumatized war veterans.